subject
Mathematics, 08.07.2019 08:10 fuenzalida73

F(x)=( x^4 + 5x^3 - 2x^2 + 5x - 3) d(x)=( x^2 + 1) divide f(x) by d(x)

ansver
Answers: 1

Another question on Mathematics

question
Mathematics, 21.06.2019 17:10
Consider the functions below. function 1 function 2 function 3 select the statement which is true about the functions over the interval [1, 2] a b function 3 has the highest average rate of change function 2 and function 3 have the same average rate of change. function and function 3 have the same average rate of change function 2 has the lowest average rate of change d.
Answers: 3
question
Mathematics, 22.06.2019 01:30
One of the solutions to x2 - 2x – 15 = 0 is x = -3. what is the other solution? ox=-5 ox= -1 0 x=1 x = 5
Answers: 2
question
Mathematics, 22.06.2019 02:30
Adoughnut shop charges $0.50 for each doughnut and $1 for a carryout box. shirley has $10 to spend. which inequality can be used to find d, the number of doughnuts she could have bought if she also wants them in one carryout box?
Answers: 1
question
Mathematics, 22.06.2019 04:00
Write a function rule for  “the output is  5 less than the input.” let  x be the input and let  y  be the output.
Answers: 1
You know the right answer?
F(x)=( x^4 + 5x^3 - 2x^2 + 5x - 3) d(x)=( x^2 + 1) divide f(x) by d(x)...
Questions